Host Defense Functions of Proteolytically Processed and Parent (Unprocessed) Cathelicidins of Rabbit Granulocytes - Zarember, Kol A. (American Society for Microbiology, 2002)
Members of the cathelicidin family are present in all mammals studied. Generally, these proteins contain a conserved N-terminal domain and a structurally and functionally divergent C-terminal region that expresses antibacterial or other activities when proteolytically released. Rabbit granulocytes produce CAP18, a cathelicidin that conforms to this structural and functional organization, and also 15-kDa protein isoforms (p15s) that share several key structural features with other cathelicidins but apparently do not undergo processing with release of an active peptide. To further define the importance of proteolysis in the antibacterial activities of these proteins, we have purified from granulocytes proCAP18, its C-terminal peptide (CAP18p), and two p15 isoforms to apparent homogeneity. Of these four polypeptides, only CAP18p was independently cytotoxic to encapsulated Escherichia coli (90% inhibitory concentration, ∼600 nM) but it was ∼50-fold less potent on a molar basis than the bactericidal/permeability-increasing protein (BPI). However, all four cathelicidin species, notably including proCAP18, exhibited antibacterial synergy with BPI, and the p15s also displayed synergy with CAP18p in the absence of BPI. Subnanomolar concentrations of proCAP18 blocked lipopolysaccharide-induced chemiluminescence of human leukocytes, showing a molar potency more than 100-fold greater than that of CAP18p (∼20 nM) or BPI (∼50 nM). Thus, while independent bactericidal activity of cathelicidins requires processing, other host-defense functions do not and are more potently expressed by the unprocessed protein than by the C-terminal peptide.